Epilepsy-surgery for fronto-basal lesions: Management, outcome, and review of literature - Grote, Alexander; Delev, Daniel; Hoffmann, Hendrik; Elger, Christian; von Lehe, Marec (Seizure-European Journal of Epilepsy, 2024)
Background: In this study, we isolated a cohort of patients who have refractory epilepsy who underwent surgery with frontobasal focus. This work aimed to develop prognostic factors associated with a better seizure outcome and identify risk factors determining postoperative morbidity. Methods: We identified all patients with frontobasal epilepsy who underwent surgery due to refractory epilepsy at the University Hospital Bonn over 22 years. Although this is a retrospective study, all data sets were collected prospectively. We evaluated both surgical and functional outcomes. Results: In total, 32 patients were identified for inclusion in this study. With a long and stable postoperative seizure outcome averaging 109 months, we were able to show that patients with frontobasal epilepsy can achieve a better outcome (53 % seizure-free, ILAE1) than patients with frontal epilepsy. In contrast to other brain regions, the resection size (isolated or extended) did not influence the outcome. Low-grade tumors, on the other hand, were associated with a better seizure outcome, and gliosis or non-specific histological findings with a worse seizure outcome. Stereo-EEG with depth electrodes is more suitable for invasive diagnostics at the frontal base than strip or grid electrodes. Patients who did not become seizure-free after surgery and underwent a second surgery did not profit significantly concerning seizure outcome. Conclusion: Patients with frontobasal epilepsy who are operated on early in the course of the disease, are MRI-positive, and have a tumor as an epileptogenic pathology have the best chance of seizure freedom.
CRIS-Team Scopus Importer:2024-11-22
Keywords: Epilepsy; Frontobasal; Seizure freedom; Surgical treatment